Protective effect of medicinal plants and Bacillus licheniformis BCR 4-3 on white shrimp (Litopenaeus vannamei) challenged with Vibrio parahaemolyticus - Valdez Chavez, Karime A; Luna González, Antonio; González Ocampo, Héctor A; Escamilla Montes, Ruth; Orozco Medina, Cesar; Fierro Coronado, Jesús A (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Up to 100% mortality can occur in shrimp farming due to viral and bacterial diseases. Prophylactic methods to decrease mortality, such as natural additives that do not generate bacterial resistance and environmental problems, are currently under research. Objective: To evaluate the effect of medicinal plants (aloe, basil, ginger, and garlic) and Bacillus licheniformis BCR 4-3 added to the water on the survival of Litopenaeus vannamei shrimp challenged with Vibrio parahaemolyticus IPNGS16. Methods: Two bioassays assessed a mixture of the four powdered plants (4 g/kg of feed) every two days, and the bacillus (1×106, 2×106 and 3×106 CFU/L) added to the water was evaluated every three and seven days. Before each bioassay, the mean lethal concentration of Vibrio was determined. Results: The mixture of medicinal plants in the feed and B.licheniformis BCR 4-3 in the water increased up to 70% the survival rate of Litopenaeus vannamei challenged with V.parahaemolyticus IPNGS16, representing a potential tool for preventing acute hepatopancreatic necrosis disease (AHPND) infections in commercial shrimp farms.